Utility of Serum Uric Acid to High-Density Lipoprotein Ratio in Prediction of Glycemic Control - Chinnusamy, Manokaran; Vishwanathan, Ram Arvind; Janakiraman, Sathiyanarayanan; Elayidath, Roshna (Journal of Health and Allied Sciences NU, 2022)
Introduction India has witnessed diabetes as a growing problem and is on the verge of a diabetes mellitus (DM) epidemic. Glycemic control is the way to prevent the morbidity associated with diabetes. This study aimed to find out the utility of uric acid to the high-density lipoprotein (HDL) ratio (UHR) as a marker of diabetic control.Methodology A hospital-based cross-sectional study was conducted among type-2 diabetic individuals who attended outpatient clinics and individuals who admitted to the inpatient wards of our hospital were enlisted. HDL cholesterol, serum uric acid, glycated hemoglobin were performed. Hemoglobin A1c (HbA1c) lower than 7% was classified as a good-controlled type-2 (DM) group and those with HbA1c between 7 and 10% were classified as uncontrolled type-2 DM group and those with HbA1c greater than 10% were classified as poorly controlled type-2 DM group. HbA1c was correlated with HDL, serum uric acid, and UHR.Results Our study demonstrates that uric acid is inversely related to HbA1c and uric acid decreases following elevated HbA1c, and this relationship was statistically significant, whereas there was a nonsignificant inverse relationship between HDL and HbA1c and UHR with HbA1c.Conclusion Established diabetics will have a lowering of uric acid as the diabetic control worsens and UHR could not be used as a marker of diabetic control.
Keywords: diabetes mellitus; uric acid to high-density lipoprotein ratio; serum uric acid; high-density lipoprotein